A Localized Model for Branding in the Iranian Dairy Industry - Shaghayegh Sabaghi; Alireza Rousta; Farzad Asayesh (‫مدیریت بازرگانی)
ObjectiveBranding is the process of creating a strong awareness of a product or service in the market using a logo, design, symbol, or slogan i.e. the elements used in advertising. Branding includes creating effective communication between a company and its customers. It has a positive and substantial impact on the customer's mind. The absence of a specific branding model can be interpreted as a primary factor contributing to the disregard of branding activities by dairy company managers. Over the past two decades, there has been a substantial increase in the number of active companies within the dairy industry, driven by shifts in consumption patterns. This surge has led to a sharp rise in competition among these companies. In such a situation, having a branding strategy can act as an important factor in increasing the competitiveness of dairy companies. With the increase in competition in the Iranian dairy market, there is an urgent need for branding to maintain a competitive position in this industry. This study was carried out to propose a local model for branding in Iran's dairy industry. MethodologyThis developmental-fundamental research was carried out using a qualitative approach and conducted as a cross-sectional study. Creswell and Clark (2007) were referenced in designing a paradigm model based on grounded theory. The data were collected through semi-structured interviews with experts from Iran's dairy industry. The statistical population in the qualitative phase comprised of 12 managers of Iranian dairy companies, including experts and specialists in the dairy industry. The primary method of data collection involved conducting semi-structured interviews. A grounded theory approach using MAXQDA v.10 software was used to analyze qualitative data and present a paradigm model. FindingsBased on the results of qualitative analysis, six categories of factors including causal conditions, contextual factors, strategies, central phenomenon, intervening factors, and consequences were identified. The macro-environment and competitive atmosphere were identified as the main components in the contextual category. Regarding causal conditions, two main categories including marketing mix, mental paradigms of managers, social responsibility, optimal mining, and organizational culture were identified. Considering strategic brand management as a central research phenomenon, brand personality indicators, brand culture, brand audit, brand participation, brand performance, and brand building were identified. Customer relationship management, brand equity, and target market selection were identified as the main categories of strategies and actions. Sustainable competitive advantage and employee participation have been identified as the most important intervening factors. Marketing performance (brand loyalty, customer satisfaction, increased market share, and increase in the number of customers) as well as financial performance (profitability and increase in sales) were identified as the main outcomes. ConclusionBased on the findings of this research, adopting a comprehensive branding model in dairy companies has the potential to enhance both market and financial performance.